Are personal characteristics of massage therapists associated with their clinical, educational, and interpersonal behaviors? - Boulanger, PhD, CMT, Karen; Campo, PhD, Shelly (International Journal of Therapeutic Massage & Bodywork, 2013)
Background: Social Cognitive Theory suggests that characteristics of health professionals, such as their beliefs in the effectiveness of their care, influence their behavior. Studying the characteristics of massage therapists may, therefore, provide insight into their clinical, educational and interpersonal behavior, which ultimately affects their client interactions.Purpose: To examine the association of three personal factors (outcome expectations, expectancies, and practice experience) of the massage therapist and the practice environment with the frequency of three interventional behaviors (clinical, educational, and interpersonal) using Social Cognitive Theory as a theoretical framework.Methods: A random sample of licensed massage therapists in Iowa completed a mailed questionnaire. Questions included training in massage, use of specific massage techniques and practices, 11 outcome expectations, and 17 different behaviors with their respective expectancies for contributing to favorable client outcomes. Factor analyses were conducted on the behavior and expectancy items. Regression analyses were used to examine the relationship of massage therapist characteristics to the different categories of behavior.Results: The response rate was 40% (N = 151). The most common techniques employed were Swedish massage, trigger point therapy, and stretching. The most common practices recommended to clients were encouraging water intake, heat application, stretching, stress management, and exercise counseling. Expectancies was the only Social Cognitive Theory variable that significantly predicted the frequency of every category of behavior (clinical, interpersonal, education; all ps < .01). Outcome expectations predicted clinical (p = .03) and educational (p < .01), but not interpersonal behavior. No other associations reached statistical significance.Conclusions: Massage therapists’ belief in massage to enact a favorable change in a client is strongly associated with their clinical, educational, and interpersonal behavior. Massage therapists were optimistic regarding the ability of massage to provide a favorable outcome, especially if the desired outcome was supported by research.